A comparison of the solvation power of the green solvent 2, 2, 5, 5-tetramethyloxolane versus toluene via partition coefficients. (10th December 2019) - Byrne, Fergal P.; Hodds, William M.; Shimizu, Seishi; Farmer, Thomas J.; Hunt, Andrew J.
Abstract: 2, 2, 5, 5-tetramethyloxolane [previously published as 2, 2, 5, 5-tetramethyltetrahydrofuran (TMTHF)] has recently been demonstrated as a greener and cleaner alternative to toluene in several applications. Assessing similarities in properties of toluene and 2, 2, 5, 5-tetramethyloxolane is crucial for establishing this molecules potential to replace traditional non-polar organic solvents in the cleaner production of chemicals and materials. However, the Hansen solubility parameters (HSP) and Kamlet-Taft parameters (KT) give conflicting views on their similarities and differences, which necessitates a full comparative characterisation of the solvation environment of these two solvents. Such comparisons have been achieved through a direct and extensive determination of partition coefficients between each of the two solvents and water. The partition coefficients and Abraham's solvation parameter model have quantitatively clarified the similarities and differences in properties of 2, 2, 5, 5-tetramethyloxolane and toluene. Solutes of high dipolarity and hydrogen-bond accepting ability tended to favour the aqueous phase in both systems, while large molar volume and high refractive indices favoured the organic phase. A significant difference between 2, 2, 5, 5-tetramethyloxolane and toluene was observed for hydrogen-bond donating solutes. In general, such solutes strongly preferred the aqueous phase in the toluene/water system but preferred the organic phase in the 2, 2, 5, 5-tetramethyloxolane/water system. This was due to the interaction of the protic solutes with the lone pairs of electrons on the ethereal oxygen of 2, 2, 5, 5-tetramethyloxolane, a feature that is not present on toluene, and opens up new possibilities for applications of this sustainable solvent in liquid-liquid extraction, particularly in the isolation of natural products. As toluene is such an important solvent in the chemical industry, its replacement with a greener alternative such as 2, 2, 5, 5-tetramethyloxolane would be hugely significant for cleaner synthesis, extractions and separations. Graphical abstract: Image 1 Highlights: Understanding properties of solvents is vital to enable sustainable industrial use. Partition coefficients quantify similarities in properties of TMO and toluene. Abraham's model indicated TMO's preference for hydrogen-bond donating solutes. TMO's lone pairs promotes dissolution of protic solutes compared to toluene. Basicity of TMO promotes its use as a green solvent in cleaning or extraction.